Resolusi Konflik Dalam Kearifan Lokal: Analisis Tradisi Perumah Begu Di Desa Juma Tombak, Deli Serdang - Clara Filipi Purba (Jurnal Pengetahuan Sosial dan Sejarah, 2026)
This study aims to examine the local wisdom values contained in the Perumah Begu tradition in Juma Tombak Village, Deli Serdang Regency, as a form of spirit-based conflict resolution. The Perumah Begu tradition is one of the cultural heritages of the Karo community that is still preserved today and is believed to play an important role in maintaining social harmony within society. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results show that the Perumah Begu tradition contains various local wisdom values, such as deliberation, social solidarity, respect for ancestors, and peace, which serve as guidelines in community life. This tradition also functions as a customary conflict resolution medium that is more easily accepted by the community because it is closely related to local beliefs and cultural values passed down from generation to generation. The existence of the Perumah Begu tradition proves that local wisdom still has an important role in maintaining social relationships and strengthening community cohesion amid modernization. This study is expected to contribute to the development of cultural history studies and the preservation of local traditions in Karo society.